2022
DOI: 10.3390/biom12050731
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomal Insights of Heart Failure from Normality to Recovery

Abstract: Current management of heart failure (HF) is centred on modulating the progression of symptoms and severity of left ventricular dysfunction. However, specific understandings of genetic and molecular targets are needed for more precise treatments. To attain a clearer picture of this, we studied transcriptome changes in a chronic progressive HF model. Fifteen sheep (Ovis aries) underwent supracoronary aortic banding using an inflatable cuff. Controlled and progressive induction of pressure overload in the LV was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
2
2
0
3
Order By: Relevance
“…The study also investigated the single-nucleus transcriptome in cardiomyocytes and non-myocyte cell types and showed metabolic pathways were profoundly impaired in DCM cardiomyocytes but not HCM cardiomyocytes, suggesting the disease-specific metabolic alteration. Similarly, another paper also showed HCM- or DCM-specific impaired metabolic processes ( 67 ). Disease-specific gene sets, some of which are involved in lipid metabolism, were found to be differentially changed between DCM and HCM, such as the up-regulated APOE and the down-regulated GPT in DCM, as well as the up-regulated APOLD1 and the down-regulated STARD13 and PON3 in HCM.…”
Section: Shared and Unique Metabolic Alterations Between Dcm And Hcmmentioning
confidence: 87%
“…The study also investigated the single-nucleus transcriptome in cardiomyocytes and non-myocyte cell types and showed metabolic pathways were profoundly impaired in DCM cardiomyocytes but not HCM cardiomyocytes, suggesting the disease-specific metabolic alteration. Similarly, another paper also showed HCM- or DCM-specific impaired metabolic processes ( 67 ). Disease-specific gene sets, some of which are involved in lipid metabolism, were found to be differentially changed between DCM and HCM, such as the up-regulated APOE and the down-regulated GPT in DCM, as well as the up-regulated APOLD1 and the down-regulated STARD13 and PON3 in HCM.…”
Section: Shared and Unique Metabolic Alterations Between Dcm And Hcmmentioning
confidence: 87%
“…[ 34 ] Previous studies have shown that the GnRH pathway is involved in the development of cardiomyopathies. [ 35 ] Toll-like receptors, as key factors that regulate innate immune responses, can lead to acute and chronic inflammation. [ 36 ] Inflammation is a characteristic feature of cardiac hypertrophy and mediates the important roles of toll-like receptors in the HCM process.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время развитие СН -это динамический процесс, в ходе которого происходит каскад метаболических изменений в миокарде и организме в целом. При моделировании прогрессирующей ХСН на овцах выявлены различия в экспрессии генов в миокарде на разных стадиях развития данного патологического состояния: по сравнению с контролем (до начала эксперимента) на стадии дилатации изменялась экспрессия 73 генов, на стадии гипертрофии -210 генов, при развитии СН -56 генов [10]. Большинство генов с измененной экспрессией на разных стадиях были уникальными и лишь незначительная их часть -общими для разных стадий.…”
Section: полигенный контроль снunclassified
“…Большинство генов с измененной экспрессией на разных стадиях были уникальными и лишь незначительная их часть -общими для разных стадий. При этом изменения в экспрессии носили обратимый характер, так как на стадии восстановления транскриптомные профили миокарда в значительной степени соответствовали таковым на стадии до начала проведения эксперимента [10]. Обратимость молекулярных изменений при развитии СН указывает на возможность управления данным патологическим процессом в случае выявления ключевых молекулярных событий.…”
Section: полигенный контроль снunclassified
See 1 more Smart Citation